THE EFFECT OF A PROJECT- BASED PROGRAM TO DEVELOP THE OF CRITICAL AND CREATIVE THINKING SKILLS - Al-Hassawi, Fatema Yousef; Al-Zaghul, Imad Abdul; Al-Jassim, Fatima Ahmed (PEOPLE: International Journal of Social Sciences, 2020)
The purpose of the current study was to identify the effectiveness of a Project-Based Program in developing Critical and Creativity Thinking Skills, Self-Concept and School Readiness among Gifted Kindergarten Children. The researcher used a quasi-experimental design. The sample consisted of (22) childs and were divided into two groups as experimental and control group. Critical thinking scale Al-ferian (2013), also Torrance scale of innovative thinking in performance and movement to measure creative thinking. The results showed statistically significant differences in some critical thinking skills such as observation, similarity, difference, judgments, and overall grade between the experimental and control groups in favor of the experimental, while statistically significant differences showed some critical thinking skills such as observation, arrangement, division, division, judgment, and overall grade between the pre and posttests. For the benefit of the post test, and there were statistically significant differences in creativity thinking skills (fluency, originality, and imagination), which indicates that the Project-Based Program was effective on critical thinking, creativity thinking skills.